What Is Typical Is Good - Sofer, Carmel; Dotsch, Ron; Wigboldus, Daniel H. J.; Todorov, Alexander (Psychological Science, 2015)
The role of face typicality in face recognition is well established, but it is unclear whether face typicality is important for face evaluation. Prior studies have focused mainly on typicality’s influence on attractiveness, although recent studies have cast doubt on its importance for attractiveness judgments. Here, we argue that face typicality is an important factor for social perception because it affects trustworthiness judgments, which approximate the basic evaluation of faces. This effect has been overlooked because trustworthiness and attractiveness judgments have a high level of shared variance for most face samples. We show that for a continuum of faces that vary on a typicality-attractiveness dimension, trustworthiness judgments peak around the typical face. In contrast, perceived attractiveness increases monotonically past the typical face, as faces become more like the most attractive face. These findings suggest that face typicality is an important determinant of face evaluation.